A Novel and Simplified Score for Determining Treatment Eligibility for Patients with Chronic Hepatitis B - Tanawat Geeratragool; Pisit Tangkijvanich; Supot Nimanong; Siwaporn Chainuvati; Phunchai Charatcharoenwitthaya; Tawesak Tanwandee; Watcharasak Chotiyaputta (Viruses, 2023)
Background: International guidelines for hepatitis B infection (HBV) recommend initiating antiviral treatment based on viral replication with inflammation or fibrosis. HBV viral loads and liver fibrosis measurements are not widely available in resource-limited countries. Aim: To develop a novel scoring system for the initiation of antiviral treatment in HBV-infected patients. Methods: We examined 602 and 420 treatment-naïve, HBV mono-infected patients for derivation and validation cohorts. We performed regression analysis to identify parameters associated with the initiation of antiviral treatment based on the European Association for the Study of the Liver (EASL) guidelines. The novel score was developed based on these parameters. Results: The novel score (HePAA) was based on HBeAg (hepatitis B e-antigen), the platelet count, alanine transaminase, and albumin. The HePAA score showed excellent performance, with AUROC values of 0.926 (95% CI, 0.901–0.950) for the derivation cohort and 0.872 (95% CI, 0.833–0.910) for the validation cohort. The optimal cutoff was ≥3 points (sensitivity, 84.9%; specificity, 92.6%). The HePAA score performed better than the World Health Organization (WHO) criteria and the Risk Estimation for HCC in Chronic Hepatitis B (REACH-B) score, and it performed similarly to the Treatment Eligibility in Africa for HBV (TREAT-B) score. Conclusions: The HePAA scoring system is simple and accurate for chronic hepatitis B treatment eligibility in resource-limited countries.